DIGITASI: SEBAGAI UPAYA PENYELAMATAN ARSIP PANDEMI COVID-19 - Ika Nur Azizah; Suci Ramadhani Nalole (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2023)
The pandemic archive has historical value so it needs to be managed properly as the nation's collective memory. So that someday if similar events can be reused as a means of decision making. One of the efforts to save pandemic archives is by digitizing archives. The purpose of this research is to produce guidelines for digitizing pandemic archives. This study uses a qualitative method. While the data collection technique is carried out by studying literature, namely by collecting some literature from international journals that discuss archival digitai. The results obtained are, in digitizing pandemic archives, several steps are carried out, namely in digitizing pandemic archives it is necessary to prepare equipment and software. There are eight criteria that must be followed for the digitization process, namely: First, a selection is made to select the material source requirements. The second determines the technical requirements and implementation. Third, pay attention to legal aspects. The fourth is funds. The fifth is human resource planning. The sixth is the development and maintenance of the interface. The eighth is to have project management. In addition, there are several stages carried out in the archive digitization process, namely: handling training, document support, removing staples, pins, and paper notes, holding seals, keeping documents organized, annotation and labeling, paying attention to scanning areas, wearing gloves, equipment, cleaning fluids, and related items, pay attention to image capture and image quality, and embed metadata.